Money creation under full-reserve banking: A stock-flow consistent model - Patrizio Lainà (Levy Economics Institute of Bard College, 2015)
This paper presents a stock-flow consistent model+ of full-reserve banking. It is found that in a steady state, full-reserve banking can accommodate a zero-growth economy and provide both full employment and zero inflation. Furthermore, a money creation experiment is conducted with the model. An increase in central bank reserves translates into a two-thirds increase in demand deposits. Money creation through government spending leads to a temporary increase in real GDP and inflation. Surprisingly, it also leads to a permanent reduction in consolidated government debt. The claims that full-reserve banking would precipitate a credit crunch or excessively volatile interest rates are found to be baseless.
Keywords: E27; E42; E51; 330; Full-reserve Banking; Stock-flow Consistency; Money Creation; Banking System